2013
DOI: 10.1016/j.freeradbiomed.2013.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Reaction of superoxide radicals with glycosaminoglycan chloramides: a kinetic study

Abstract: Hypochlorous acid and its acid-base counterpart, hypochlorite ions, produced in inflammatory conditions, may produce chloramides of glycosaminoglycans, perhaps through the binding of myeloperoxidase directly to the glycosaminoglycans. The N-Cl group in the chloramides is a potential target for reducing species such as Cu(I) and superoxide radicals. Laser flash photolysis has been used here to obtain, for the first time, the rate constants for the direct reaction of superoxide radicals with the chloramides of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 54 publications
1
7
0
Order By: Relevance
“…However, not all biologically relevant radicals induce GAG chain breaks. In a laser flash photolysis study (performed at pH = 8.5), the reaction between O 2 and HA or heparin only showed O 2 dismutation, implying very low or no reactivity of O 2 toward these GAGs (109). Subsequent fragmentation studies confirmed the lack of reactivity and (direct) GAG fragmentation by O 2 -(132).…”
Section: Mechanisms Of Gcx Oxidationmentioning
confidence: 87%
“…However, not all biologically relevant radicals induce GAG chain breaks. In a laser flash photolysis study (performed at pH = 8.5), the reaction between O 2 and HA or heparin only showed O 2 dismutation, implying very low or no reactivity of O 2 toward these GAGs (109). Subsequent fragmentation studies confirmed the lack of reactivity and (direct) GAG fragmentation by O 2 -(132).…”
Section: Mechanisms Of Gcx Oxidationmentioning
confidence: 87%
“…It is thus difficult at present to reconcile the kinetic data [42], the SOTS-1 studies [23,27] and the fragmentation data presented here. It may be that superoxide reduces the chloramide directly, as confirmed for other reducing radicals in the previous kinetic study [41] to produce the amidyl radical which may react rapidly with oxygen to produce a nitroxide species as found in previous studies of sterically-hindered amidyl and aminyl radicals [43,44].…”
Section: Resultsmentioning
confidence: 63%
“…The weak reducing agent, the superoxide radical was produced by the irradiation of oxygen-saturated 0.1mM and 0.8mM chloramide ( HACl) and 0.4mM chloramide (HepCl ) solutions containing 0.1M formate at pH 9.5, as in reactions (1) and (3) [42]. Despite this demonstration of a reaction, it would appear from the current study that it does not lead to fragmentation of HACl.…”
Section: Resultsmentioning
confidence: 63%
See 1 more Smart Citation
“…[33][34][35][36][37][38][39][40] Due to its outstanding oxidative power, this species can significantly alter the activities and availabilities of biomolecules.…”
Section: Introductionmentioning
confidence: 99%